THE EFFECTIVENESS OF CLASS DISCUSSION LEARNING METHOD BY USING CISCO WEBEX APPLICATION IN IMPROVING STUDENTS’ SPEAKING SKILLS AND LEARNING OUTCOMES AT THE ENGLISH LANGUAGE DEPARTMENT OF UNIVERSITY OF MUHAMMADIYAH TANGERANG - Muhammad Saleh Taher, J. Anhar Rabi Hamsah Tis’ah (IJLECR (International Journal of Language Education and Cultural Review), 2020)
Abstract This study aims to determine the effectiveness of the use of class discussion learning models by using the Cisco Webex application in improving students’ speaking skills and learning outcomes at the University of Muhammadiyah Tangerang. The research method was used a quasi-experimental research method with the research samples were students who took the speaking subject in the English Study Program. The research design used pretest and posttest control group design. A different test was conducted to measure the differences in the effectiveness of using learning media of Cisco Webex application and using of other applications learning media based on learning outcomes. It can be concluded that the level of effectiveness of class discussion method using of Cisco Webex application learning media in the experiment class is higher than the control class using other applications learning media 82.25 > 80.52.